Absorption Properties of Pr3+ -doped Fluoroborate and Boro-Tellurite Glasses - Thyagarajan, K.; Buddhudu, S. (Asian Journal of Chemistry, 2010)
This paper reports the preparation and spectral analysis of two series of Pr3+ -doped glasses of the compositions: Fluoroborate glasses: B2O3-Na2O-RF ( = LiF and NaF) Borotellurite glasses: B2O3-BaO-TeO2-RF (= Li, NaF and KF) The computed parametrization of both the physical and the nonlinear spectra demonstrates the effects of alkali cations (Li, Na and K) in the glasses studied.